Techno-economic Assessment of Battery Energy Storage Systems in Renewable Energy Communities - Barata, Filipe; Sousa, Jorge; Viveiros, Carla; Perinhas, Sérgio (International Journal of Sustainable Energy Planning and Management, 2025)
Renewable Energy Communities (RECs) are an important driver in the energy transition to foster renewables deployment in a cost-effective way, to engage citizens in the energy sector with an active participation, to share local energy, and to improve local balancing. A key element to maximize the utilization of renewable resources is the ability to store energy in renewable energy communities. By storing excess energy, communities can avoid curtailment, which occurs when renewable energy generation exceeds the immediate demand. This curtailed energy can be stored for later use which optimizes the functioning of an integrated system. This study highlights the cost-effectiveness of implementing Battery Energy Storage Systems (BESS) in the framework of REC. Findings support the potential benefits even when employing lower-efficiency storage systems, provided their costs are sufficiently low. Results show that, at the current level of technological development, BESS are not economically viable without additional revenue streams. It is also shown that BESS could be economically feasible in the future with anticipated technological development that would drive Capital Expenditure (CAPEX) down. Under these circumstances, cost savings are enhanced in the REC context, as members’ energy storage capacities are shared within the community along with the renewable energy generation.